1981
DOI: 10.1007/bf01908360
|View full text |Cite
|
Sign up to set email alerts
|

Curvilinearity of the diastolic pressure-flow relationship in autoregulating and maximally vasodilated coronary beds; effects on estimates of zero-flow pressure and differences between zero-flow and intracavitary diastolic pressures. Role of capacitive effects in the determination of zero-flow pressure from long diastoles

Abstract: Bellamy's recent studies (1) suggest that coronary driving pressure is overestimated importantly when downstream pressure is taken as right atrial or left ventricular diastolic pressure. In these provocative observations the relationship between instantaneous left circumflex (LC) inflow and pressure showed a high correlation coefficient and was taken as linear over the range of pressure studied; extrapolation was frequently required in the determination of the pressure at which inflow ceased, i.e., the pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Earlier experimental and clinical studies investigating the effects of massive coronary vasodilatation on diastolic P-F demonstrated that the linearity of the relationship between pressure and flow velocity was not influenced. The slope increased and COP decreased after vasodilatation in these studies (Dole et al 1984;Klocke et al 1981;Nanto et al 2001).…”
Section: Discussionsupporting
confidence: 51%
“…Earlier experimental and clinical studies investigating the effects of massive coronary vasodilatation on diastolic P-F demonstrated that the linearity of the relationship between pressure and flow velocity was not influenced. The slope increased and COP decreased after vasodilatation in these studies (Dole et al 1984;Klocke et al 1981;Nanto et al 2001).…”
Section: Discussionsupporting
confidence: 51%
“…Figure 6 shows the steady state, or autoregulation curve, together with instantaneous pressure-flow relationships as determined from a range of steady-state pressures (36). The instantaneous relationships in general appear to be straight (36) or curvilinear (237,238) with a so-called zero-flow pressure intercept, P fϭ0 , i.e., with negligible flow, pressure is still present. The inverse of the slope of the instantaneous pressureflow relationship is the instantaneous resistance (R i ).…”
Section: Instantaneous Pressure-flow Relationship and Zero-flow Pressmentioning
confidence: 99%
“…The instantaneous resistance and the intercept pressure both depend on the vasoactive state of the coronary bed. For increased perfusion pressure, the vasculature constricts as a result of autoregulation, and the resistance and intercept of the instantaneous pressure-flow relation increase, thereby keeping mean flow in the steady-state constant (107,238). In humans, the zero-flow pressure intercept of the instantaneous pressure-flow relation is ϳ40 mmHg in control and ϳ15 mmHg in vasodilation (307).…”
Section: Instantaneous Pressure-flow Relationship and Zero-flow Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier experimental and clinical studies investigating the effects of massive coronary vasodilatation on diastolic P-F demonstrated that the linearity of the relationship between pressure and flow velocity was not influenced. The slope increased and COP decreased after vasodilatation in these studies ( Dole et al, 1984 ; Klocke et al, 1981 ; Nanto et al, 2001 ). Intracoronary injections of angiographic contrast medium or adenosine triphosphate depressed vasomotor activity and induced an atrioventricular blockade followed by a non-physiological increase in diastole.…”
Section: Discussionmentioning
confidence: 52%